A novel geographic population of Dasyhelea ludingensis Zhang & Yu from Guizhou Province, China (Diptera: Ceratopogonidae) - Jiang, Xiaohong; Xie, Yao; Chen, Tingting; Li, Zhuoyue; Zhang, Guojiang; Liu, Qiongyou (Zootaxa, 2025)
The study presents a report on the intraspecific variation among female adults of Dasyhelea ludingensis Zhang & Yu. Specimens were collected using a Malaise trap near a pond in Honghuagang District, Zunyi City, Guizhou Province, China. Morphological structures were examined utilizing both optical microscopy and scanning electron microscopy. The partial mitochondrial Cytochrome oxidase I (COI) was used to analyze the genetic relationships among samples. Dasyhelea ludingensis should be classified as a species with significant intraspecific morphological variation, as supported by the molecular and morphological data.